Attitudes to genetically modified food over time: How trust in organizations and the media cycle predict support. (July 2015) - Marques, Mathew D.; Critchley, Christine R.; Walshe, Jarrod
This research examined public opinion toward genetically modified plants and animals for food, and how trust in organizations and media coverage explained attitudes toward these organisms. Nationally representative samples ( N = 8821) over 10 years showed Australians were less positive toward genetically modified animals compared to genetically modified plants for food, especially in years where media coverage was high. Structural equation modeling found that positive attitudes toward different genetically modified organisms for food were significantly associated with higher trust in scientists and regulators (e.g. governments), and with lower trust in watchdogs (e.g. environmental movement). Public trust in scientists and watchdogs was a stronger predictor of attitudes toward the use of genetically modified plants for food than animals, but only when media coverage was low. Results are discussed regarding the moral acceptability of genetically modified organisms for food, the media's role in shaping public opinion, and the role public trust in organizations has on attitudes toward genetically modified organisms.